Cold Plasma: The Way to Improve the Repeatability of Sald ICP-MS Analysis - Stiborek Marek (Hungarian Journal of Industry and Chemistry, 2018)
This work deals with the preparation of model biological microsamples for Substrate-Assisted Laser Desorption Inductively Coupled Plasma Mass Spectrometry (SALD ICP-MS). This technique provides the direct and fast analysis of liquid samples deposited onto polyethylene terephthalate (PET) plates (substrates) in the form of dried droplets with minimal sample preparation and submicrolitre sample volume requirements. Furthermore, SALD ICP-MS allows for the direct analysis of samples in organic solvents, which cannot be directly nebulised to ICP-MS. These benefits are, however, balanced out by the low degree of repeatability of the assay, which is typically about 30%. One of the approaches to increase the repeatability is a modification of the substrate surface by Diffuse Coplanar Surface Barrier Discharge (DCSBD) with the addition of an internal standard to the sample. Using this approach, a relative standard deviation (RSD) of less than 10% for model biological samples can be achieved. The only limitation of this technique is the occurrence of the so-called “aging effect”, i.e. the gradual return of the modified physicochemical surface properties to their original state